Niosome as a Novel Pharmaceutical Drug Delivery: A Brief Review Highlighting Formulation, Types, Composition and Application - Umbarkar, Mahesh Gajanan (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: Formation of niosome by using non-ionic surfactant. The particle size of niosome must be required in the range in between 10 nm -100 nm. This is just due to avoid the aggregation of niosome and show proper result. Materials and Methods: There are many types of niosome, their types and size depend on which method used for preparation. In this article we covered method of preparation of pro-niosome and niosome. Many factors are affecting formation of niosome such as drugs, its chemical and physical property, amount and type of surfactant, cholesterol content and its charge, resistance to osmatic stress as well as membrane composition. Various method is used for separation of unentrapped drug from final product such as dialysis, gel filtration and centrifugation. There are several routes used for administration of niosome such as oral, parenteral, transdermal and ocular etc. Results: The evaluation and characterization of niosome done by many methods such as entrapment efficacy, vesicle diameter, in-vitro release and loading efficiency. Niosome have many pharmaceutical and non-pharmaceutical applications; which having marketed product of niosome are available in market are explain in this article. Conclusion: Niosome formation methods are completely based on liposome methods of preparation. Niosome are having more storage capacity than liposome i.e. niosome are more advance than liposome. The cost of preparation of niosome is also less than liposome. Many pharmaceutical formulations of niosome are now available in market
Keywords: Niosome; Pro-niosome; Non-ionic surfactant; Preparation; Application